Psychological injury as a factor of mental disorders - T. Taran (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The article examines the phenomenon of mental trauma that caused participation in hostilities and living in areas which are military actions. An clinical cases of patients suffering from post-traumatic stress disorder, analyzed the etiology of their symptoms.